Effects of survival processing on list method directed forgetting. Issue 5 (28th May 2021) - Parker, Andrew; Parkin, Adam; Dagnall, Neil
ABSTRACT: Two experiments examined the effects of directed (intentional) forgetting on information processed for its survival value. Experiment 1 used the list-method directed forgetting procedure in which items processed for their relevance to survival, moving house or pleasantness were followed by the cue to remember or forget. Following the encoding of a second list, free-recall of both lists showed that survival encoding brought about greater remembering (after the remember cue) and forgetting (after the forget cue). Experiment 2 also used the list-method and manipulated mental context reinstatement prior to recall. Although this manipulation was effective in enhancing memory, more directed forgetting was again shown in the survival condition. In both experiments the effects of survival processing were shown also in free-recall "remember" (vs. "know") responses, indicative of the retrieval of associative or contextual details. The mechanisms that might underpin these were evaluated and considered in relation to future work.